2018
DOI: 10.1016/j.schres.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch negativity impairment is associated with deficits in identifying real-world environmental sounds in schizophrenia

Abstract: Impairments in early auditory information processing in schizophrenia account for significant proportions of variance in the ability to identify real-world, functionally relevant environmental sounds. This study supports the view that interventions targeting deficits in low-level auditory sensory processing may also impact more complex cognitive brain processes relevant to psychosocial disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
0
16
0
4
Order By: Relevance
“…Deficits in EAP have been extensively studied in patients with schizophrenia, where they are thought to contribute to failures in detecting important environmental cues and filtering of irrelevant stimuli, possibly leading to social withdrawal, hallucinations, cognitive dysfunction, and decreased level of overall day-to-day functioning (1,3,4,6,7,9,10,12,19,88,100,114,168). Here, we reviewed studies examining if MMN and P50 meet the 5 criteria for a marker to be considered an endophenotype (46), as well as their relationship with cognitive and psychosocial functioning to examine their potential to be used as markers to inform interventions targeted at improving these domains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Deficits in EAP have been extensively studied in patients with schizophrenia, where they are thought to contribute to failures in detecting important environmental cues and filtering of irrelevant stimuli, possibly leading to social withdrawal, hallucinations, cognitive dysfunction, and decreased level of overall day-to-day functioning (1,3,4,6,7,9,10,12,19,88,100,114,168). Here, we reviewed studies examining if MMN and P50 meet the 5 criteria for a marker to be considered an endophenotype (46), as well as their relationship with cognitive and psychosocial functioning to examine their potential to be used as markers to inform interventions targeted at improving these domains.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment in MMN is consistently demonstrated in patients with schizophrenia (14,19,88) with studies showing moderate to high test-retest reliability (58,89). However, studies examining heritability, trait stability and diagnostic specificity of MMN have reported mixed findings (89,90,100) suggesting that while promising, future studies further demonstrating MMN's suitability as an endophenotype for schizophrenia would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction of auditory MMN amplitude was reported over two decades ago in SZ and has been replicated numerous times ( 37 ). MMN deficits are found in those with chronic psychosis ( 27 , 37 50 ), in unmedicated SZ patients ( 29 , 40 , 46 , 47 , 51 , 52 ), and are shown to be resistant to antipsychotics ( 46 , 53 58 ). Abnormal MMN is also found in recent-onset psychosis as well as prodromal illness ( 30 , 51 , 59 66 ).…”
Section: Mismatch Negativity: a Neurophysiological Biomarker For Earlmentioning
confidence: 99%